"A Balance That We Walk": Characteristics, Attributes, and Behaviors That Promote Healthy American Indian Heterosexual Couple Relationships. (February 2018) - Rink, Elizabeth; Ricker, Adriann; FourStar, Kristofer; Hallum-Montes, Rachel
The purpose of this study was to investigate the characteristics, attributes, and behaviors that promote healthy American Indian (AI) heterosexual couple relationships. Specific attention was given to the role AI men have in developing and maintaining healthy heterosexual couple relationships. In-depth interviews were conducted with 15 AI participants. Key themes to emerge from analysis of qualitative data included learning about healthy relationships from elders, demonstrating mutual respect and trust, showing respect for women, and honoring a "balance" between love and sex. Findings suggest that interventions for AI men that reinforce Native beliefs, values, and practices are needed to strengthen AI couple relationships.